2017
DOI: 10.1111/bcp.13295
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia risk in asthma patients using inhaled corticosteroids: a quasi‐cohort study

Abstract: ICS use in asthma patients appears to be associated with an increased risk of pneumonia and is present for both budesonide and fluticasone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 38 publications
2
51
0
6
Order By: Relevance
“…15 Nevertheless, one Canadian cohort study of patients with asthma demonstrated that current ICS use was associated with a 45% relative increased risk of pneumonia, amounting to an excess of 1.44 cases per 1000 patient-years. 16 Interestingly, ciclesonide and mometasone, but not budesonide, beclomethasone, or fluticasone, exhibit in vitro suppression of SARS-CoV-2 replication to a similar degree as lopinavir, albeit in preliminary non peer reviewed data. 17 For ciclesonide, its target on viral replication appears to be nonstructural protein 15 (NSP15).…”
mentioning
confidence: 97%
“…15 Nevertheless, one Canadian cohort study of patients with asthma demonstrated that current ICS use was associated with a 45% relative increased risk of pneumonia, amounting to an excess of 1.44 cases per 1000 patient-years. 16 Interestingly, ciclesonide and mometasone, but not budesonide, beclomethasone, or fluticasone, exhibit in vitro suppression of SARS-CoV-2 replication to a similar degree as lopinavir, albeit in preliminary non peer reviewed data. 17 For ciclesonide, its target on viral replication appears to be nonstructural protein 15 (NSP15).…”
mentioning
confidence: 97%
“…In fact, the proportion of patients with pneumonia at the index hospitalisation was around 80%. The higher incidence of COPD exacerbation in the control group may therefore be explained by the fact that ICS increases the risk of lower respiratory tract infection, including pneumonia, in patients with COPD [7,8], as well as in those with bronchial asthma [9,10]. Notably, the mean age of our study population was around 78 years.…”
Section: Discussionmentioning
confidence: 84%
“…Adverse effects including candidiasis, cataract, glaucoma, diabetes, bone fracture, and pneumonia have been associated with high-dose ICSs [6] and have been raised as an issue, particularly in elderly patients [7,8]. In addition, an increased risk of lower respiratory tract infection associated with the use of ICSs has also been reported in patients with bronchial asthma [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study, by using a quasi-cohort design, concluded that subjects with asthma were at greater risk for pneumonia if they used ICS therapy. 39 The overall risk associated with current ICS use was 1.83. The relative risk was dose related (1.6 for low dose and 1.96 for high dose), and higher for budesonide and fluticasone compared with other agents (2.67 and 1.93, respectively).…”
Section: Adverse Drug Reactions and Side Effectsmentioning
confidence: 98%